Sex- related morphometric difference in sternal index and dimensions amongst Nepalese adults - Karki, Raj Kumar; Singh, Pankaj Kumar; Karki, Subindra; Shah, Dhiraj Kumar (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: The comprehensive goal in forensic anthropology is the identification of skeletal remains for which researchers are constantly working to produce methods that are as accurate as possible. Because of distinct sexual dimorphism, bones of the pelvis and skull are preferred; however, when these bones are unavailable other bones like sternum have to be used as it holds a great deal of sexual dimorphism.Objective: To evaluate sexual dimorphism in the metric parameters of the sternum through MDCT images amongst Nepalese adults.Materials and Methods: Sternal dimensions of 105 study participants (62 male and 43 female) were measured using Computed Tomography (CT) images from Radiology Department of Dhulikhel Hospital. An independent t test was performed to assess the strength of association between different variables and genders. Differences were considered significant at P < 0.05. ROC curve analysis was done to determine the discriminating power of variables for sex determination.Result: The different measurements of sternal lengths were significantly greater in male than females(p